Menghubungkan Pengalaman Pelanggan, Kepuasan Dan Loyalitas Dengan Kekuatan Dan Kinerja Merek Di Bangka City Hotel - Susandra Putri Miharja; Sumar Sumar (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The COVID-19 pandemic has had a significant impact on the decline in hotel consumption levels. To survive and compete in the market, hotels must be able to maintain their brand strength and performance. This study aims to determine the relationship between customer experience, customer satisfaction, and customer loyalty on brand strength and brand performance in the hospitality industry. The focus is on the importance of the role of the three consumer constructs on brand value. This paper uses a descriptive research design and quantitative approach where data collection is done by distributing online questionnaires to respondents through Google Forms. The selected population is tourists who have stayed at Bangka City Hotel in Bangka Belitung, with a sample size of 170 respondents. The results showed that from the customer's point of view, customer experience has an impact on customer satisfaction which affects customer loyalty. In addition, customer loyalty is a factor that affects brand value, including brand strength and performance. Therefore, customer loyalty is a strong predictor of brand value in the hospitality and tourism industry. By strengthening this area, companies will have great resources and opportunities to build brand strength and brand performance. customer loyalty is a strong predictor of brand value in the hospitality and tourism industry.